STUDY ON TOUGHNESS OF DOMESTIC PRESSURE VESSEL STEEL Q345R AT LOW TEMPERATURE - CUI QingFeng; HUI Hu; WANG HaoYang; LI PeiNing (Jixie qiangdu)
In the present paper,the relevant provision in the ASME Code Case about"Applicability of the ASME exemption curve for Chinese pressure vessel steel Q345R"has been analyzed by using failure assessment procedure on the basis of true material testing data. For the normalized Q345 R investigated in this paper,the results indicated that both Charpy impact toughness and fracture toughness at low temperature are better than the requirements in ASME Code,the provision in ASME Code classifying Q345 R in Exemption curve A excessively underestimated the toughness of the material.